PROBLEMATIC SLOVAK DIMINUTIVES IN EDUCATIONAL PRACTICE - STOFFA, Jan (Trends in education, 2021)
The study presents problems in the use of Slovak diminutives in the practice of educators, especially techno- and infoeducators. It describes diminutives as specific terms, which are used mainly as elements of multi-word terms. It points out that in scientific-technical terminology (terminology as a set of terms) only such diminutives are to be used, which are an expression of the smallness of objects, or a small degree of something. Emotionally colored diminutives, which are an important stylistic means in colloquial or artistic style, should not be used in scientific or professional style, and therefore are not part of the scientific-technical terminology. Much of the diminutives are problem-free. These are primarily standard, and standardized diminutives as well as diminutives, which are an organic part of the terminological usage of the relevant scientific, respectively professional community. However, there are also diminutives that present a problem for many users of the terminology. The study defines individual groups of such diminutives, explains why they are problematic and their specific cases. These are non-standard, sub-standard, colloquial, homonymous, synonymous, new - neologisms, outdated, Czech, pseudo-Czech, and pseudo-diminutives. The study also contains examples of mentioned diminutives and recommendations for solving terminological problems.
Keywords: diminutives; diminutives in education; problematic diminutives